Pengaruh Media Sosial Terhadap Motivasi Belajar Mahasiswa Pendidikan Ekonomi FKIP ULM - Akmal, Muhammad Fahmi; Ratumbuysang, Monry Fraick Nicky Gillian; Hasanah, Mahmudah; Nor, Baseran (Jurnal Pendidikan Ekonomi (JUPE), 2024)
This research aims to analyze the influence of social media on the learning motivation of Economics Education Students at FKIP ULM. The research design used is quantitative research, namely research in the form of numbers and analysis using statistics with a quantitative descriptive approach. The subjects in this research were students from the Faculty of Teacher Training and Education, FKIP ULM. The sample used was 160 respondents selected using the Proportionate Stratified Random Sampling method. The analysis tool used is SPSS 25.00. Based on the results of data processing, it can be said that the influence of social media on learning motivation is 9,8% (low influence).